2010
DOI: 10.1038/ijo.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

Reduced body weight in male Tspan8-deficient mice

Abstract: Objective: The gene TSPAN8 was recently identified in a genome-wide association study as the most likely causal gene in a locus that was correlated with the risk of type 2 diabetes (T2D) in northern European individuals. To assess whether Tspan8 is the actual T2D-causal gene in this locus, we ablated its expression in mice and determined the consequences of this ablation on a multitude of metabolic traits. Results: We found that genetic ablation of Tspan8 in mice results in a reduction (À15.6%) in the body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…Loss of this gene is associated with decreased body weight, although there were no detectable effects on glucose tolerance or insulin sensitivity [79]. In contrast to that study which did not detect expression of this gene in mouse pancreas [79], we found expression of this gene in isolated pancreatic islets and suggested regulation of its expression by glucose. Tspan8 expression was significantly decreased in brains of fed compared to fasted chow-fed mice, suggesting it may also have a role in the neural control of metabolism.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Loss of this gene is associated with decreased body weight, although there were no detectable effects on glucose tolerance or insulin sensitivity [79]. In contrast to that study which did not detect expression of this gene in mouse pancreas [79], we found expression of this gene in isolated pancreatic islets and suggested regulation of its expression by glucose. Tspan8 expression was significantly decreased in brains of fed compared to fasted chow-fed mice, suggesting it may also have a role in the neural control of metabolism.…”
Section: Discussioncontrasting
confidence: 92%
“…Although some studies have found associations between SNPs in this gene and insulin sensitivity or secretion [47,57], others have not [48-50,52]. Loss of this gene is associated with decreased body weight, although there were no detectable effects on glucose tolerance or insulin sensitivity [79]. In contrast to that study which did not detect expression of this gene in mouse pancreas [79], we found expression of this gene in isolated pancreatic islets and suggested regulation of its expression by glucose.…”
Section: Discussionmentioning
confidence: 99%
“…TSPAN8 has also been identified in the bovine sperm plasma membrane (Byrne et al, ), but no function has been attributed in sperm physiology. Male Tspan8 −/− mice are fertile and viable with no major abnormalities (Champy et al, ). As highlighted by these authors, most ablation of tetraspanins leads to viable mice without major developmental abnormalities, suggesting molecular redundancy or compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Still another role for TSPAN8 is seen during kidney disease in Humans; where TSPAN8 is believed serve a protective role (Pan et al). TSPAN8 may also provide protection during cold stress by forming membrane microdomains with other proteins to maintain membrane cryostability and fluidity, which is essential for resisting low temperature stress (Champy et al;Hirukawa et al;Cossins and Prosser, 1978).…”
Section: Discussionmentioning
confidence: 99%